Status Pekerjaan Ibu dengan Perkembangan Balita Usia 3 Sampai 5 Tahun di Paud Permata Hati Al Mahalli - Nurul Oktavia Setia Utami; Era Revika; Nur’aeni Eka Sari (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2023)
ABSTRACTBackground: Children can optimally achieve 4 aspects of development (fine motor, gross motor, language, and social) if they get stimulation from an early age. Many factors affect the growth and development of children. Parents or companions can do the stimulation. Parents, especially mothers, play an essential role in the process of growth and development of children. Currently, mothers have various roles, one of which is being a working mother.Objective: This study aimed to determine the correlation between the mother's employment status and the development of toddlers aged 3 to 5 years at Permata Hati Al Mahalli Method: This is an observational analytic study with a cross-sectional approach. This study used total sampling to get 35 respondents of mothers and toddlers. Data collection was carried out using mother respondent identity sheets and the results of the Pre-screening Developmental Questionnaire (PDQ) for assessing toddler development. Data analysis in this study was carried out using Chi-Square.Result: This study showed that there were 7 (35%) toddlers with dubious development out of 20 working mothers and 1 (6.7%) toddler with dubious development out of 15 non-working mothers. The chi-square test results showed df = 1 at a significant level of 5% with a p-value of 0.048 <0.05.Conclusion: Mother's employment status is significantly correlated with the development of toddlers aged 3 to 5 years at Permata Hati Al MahalliKeywords: Mother's employment status, toddlers’ development